Forest road planning using precision geographic data under climate change. Issue 3 (2nd September 2019) - Yoshida, Mika; Sakurai, Rin; Sakai, Hideo
ABSTRACT: Frequent heavy rainfall is suspected to cause failures on spur roads especially those constructed by earthworks . It is essential to construct robust, cost-efficient and well-maintained road networks to react to uncertain events. Laser imaging detection and ranging technology (LiDAR) can measure the topography. By constructing spur roads based on the watercourse map estimated from the digital elevation model taken by LiDAR, the change of watercourses could be followed by using LiDAR after construction and spur road failures were surveyed to evaluate the road planning process. The route was selected to avoid watercourses using stable points such as natural bench. The roads crossing the watercourses were protected from surface runoff by dispersal drainage systems. The route and dispersal drainage systems effectively prevented runoff from soil erosion from a cut slope. The height of the cut slope and the stability of the natural slope were key for routing and selecting drainage systems. Spur roads with functional dispersal drainage systems at appropriate places are expected to improve the ability of water conservation in mountainous forests, which could contribute to keeping them as the "green infrastructure" and adapting to climate change.